Pendekatan Kedokteran Keluarga pada Pasien Tuberkulosis Paru - Muammar Devahran; Nathalie E. Kailola (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2026)
Pulmonary tuberculosis (TB) remains a major public health problem with a high incidence and relapse rate, particularly in developing countries such as Indonesia. The success of TB management is determined not only by pharmacological treatment but also by family, behavioral, and environmental factors. This study aimed to analyze the implementation of a family medicine approach in a patient with relapsed pulmonary tuberculosis by identifying clinical, familial, and environmental factors that influence disease progression. This study employed a case report design using a family medicine approach in a 61-year-old male patient diagnosed with relapsed pulmonary TB based on history taking, physical examination, and a positive Molecular Rapid Test (MRT) result. The findings revealed that, in addition to biological factors, several risk factors contributed to the patient's condition, including a history of smoking, close contact with individuals presenting similar symptoms, and an unhealthy home environment. Follow-up evaluations demonstrated clinical improvement following continuation-phase anti-tuberculosis treatment and family-based educational interventions. These findings suggest that a holistic and comprehensive family medicine approach plays an important role in improving treatment outcomes, preventing disease relapse, and supporting sustainable pulmonary tuberculosis control efforts.